Anteseden Reputasi Perusahaan Dan Kualitas Layananan Karyawan Pengaruhnya Terhadap Kepuasan Peserta Pensiun pada PT. Taspen (persero) Cabang Mamuju - Tahir, Muh; Ramli S, Ramli S (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
The purpose of this study 1. To determine the company's reputation antecedents on the satisfaction of pensioners at PT. Taspen (Persero) Mamuju Branch, 2. To determine the effect of employee service quality on retirement participant satisfaction at PT. Taspen (Persero) Mamuju Branch. 3. To find out which variable has the most dominant influence on the satisfaction of pension participants at PT. Taspen (Persero) Mamuju Branch. Quantitative research is an approach using lots of numbers in exploring and understanding the meaning of individual or groups of observed variables associated with a problem whose influence relationship will be known. The location of this research was carried out at the office of PT. Taspen (Persero) Mamuju Branch. In this study, researchers took a sample of 30. As a general rule, a sample size of between 30 and 500 can be effective depending on the method of sampling. Validity Test, Reliability Test, Multiple Linear Regression Test. In this study the analytical test tools used by the author are partial test and simultaneous test. The results of data analysis show that company reputation has a significant effect on the satisfaction of pension participants at PT Taspen (Persero) Mamuju Branch. Service quality has a significant effect on the satisfaction of pension participants at PT Taspen (Persero) Mamuju Branch. The most dominant service quality variable has a significant effect on the satisfaction of pension participants at PT Taspen (Persero) Mamuju Branch